War and society in the Roman world - Rich, John, 1944-; Shipley, Graham (Leicester-Nottingham studies in ancient society, 1993)
The impact of war on ancient society is the subject of this book and the companion volume, War and Society in the Greek World. Earlier studies of ancient warfare have concentrated on political causes, tactics, strategy and military organisation. In these volumes warfare is viewed rather as a species of social action, affecting and affected by social conditions and ideologies, and having social, economic and cultural consequences. The central theme of this volume is the shifting relationship between warfare and the Roman citizen body. The dominant role of war in Roman life under the Republic is examined, together with the related themes of Roman expansion and its consequences for both the Romans and those they conquered. Under the Principate expansion largely stopped and the inhabitants of the empire enjoyed the Roman peace protected by a professional army. A number of chapters focus on these changes, explaining how they came about, analysing their effect on attitudes to war and probing the extent to which the peace was a reality. The Late Empire is studied in the final chapters, which document the rise of warlords and, in the west, the final disappearance of the Roman army. This volume will be of great interest to all those concerned with Roman history, or more generally with the relationship between warfare and historical societies.